Involvement of sinoaortic afferents in renal sympathoinhibition and vasodilation induced by acute hypernatremia - Silva, Elaine F.; Sera, Celisa T. N.; Mourao, Aline A.; Lopes, Paulo R.; Moreira, Marina C. S.; Ferreira-Neto, Marcos L.; Colombari, Debora A. S. [UNESP]; Cravo, Sergio L. D.; Pedrino, Gustavo R. (Wiley-Blackwell, 2015)
Despite the abundance of evidence that supports the important role of aortic and carotid afferents to short-term regulation of blood pressure and detection of variation in the arterial PO2, PCO2 and pH, relatively little is known regarding the role of these afferents during changes in the volume and composition of extracellular compartments. The present study sought to determine the involvement of these afferents in the renal vasodilation and sympathoinhibition induced by hypertonic saline (HS) infusion. Sinoaortic-denervated and sham male Wistar rats were anaesthetised with intravenous (i.v.) urethane (1.2g/kg body weight (bw)) prior to the measurement of the mean arterial pressure (MAP), renal vascular conductance (RVC) and renal sympathetic nerve activity (RSNA). In the sham group, the HS infusion (3mol/L NaCl, 1.8mL/kg bw, i.v.) induced transient hypertension (12 +/- 4 mmHg from baseline, peak at 10min; P<0.05), an increase in RVC (127 +/- 9% and 150 +/- 13% from baseline, at 20 and 60min respectively; P<0.05) and a decrease in RSNA (-34 +/- 10% and -29 +/- 5% from baseline, at 10 and 60min respectively; P<0.05). In sinoaortic-denervated rats, HS infusion promoted a sustained pressor response (30 +/- 5 and 17 +/- 6mmHg of baseline values, at 10 and 30min respectively; P<0.05) and abolished the increase in RVC (85 +/- 8% from baseline, at 10min) and decrease in RSNA (-4 +/- 3% from baseline, at 10min). These results suggest that aortic and carotid afferents are involved in cardiovascular and renal sympathoinhibition responses induced by acute hypernatremia.
Keywords: arterial blood pressure; renal blood flow; sinoaortic denervation; sodium overload